Immunomodulatory and gene expression characterisation of human mesenchymal stem cells derived from non-osteoarthritic and osteoarthritic cartilage - Al-Graittee, Satar Jabbar Rahi (2018)
Osteoarthritis (OA) is a degenerative disease characterised by progressive loss of articular cartilage which affects millions of people globally. Although the leading causes of OA are still elusive, the increasing body of evidence indicates that the predisposing factors such as lifestyle, age, injuries and genetics associated with the onset of OA. The regeneration of the degraded cartilage tissue in OA is mediated by the tissue-resident stem cells. However, in advanced OA, the regenerative and tissue repair capability of tissue-resident stem cells is compromised as a result of diseases condition and leads to an unusual stem cell nature. Mesenchymal stem cells (MSCs) have been implicated in the pathogenesis of OA and, in turn, the progression of the disease could be therapeutically modulated by MSCs. However, it remains unclear whether the defective tissue-resident MSCs contributes to the pathogenesis of OA by a depleted stem cell pool or loss of the chondrogenic differentiation potential which impedes on the proper execution of stem cell functions. Therefore, this study aimed to explore the biological properties of human non-OA and OA cartilage-derived MSCs (C-MSCs) as well as to determine whether the defects in human OA C-MSCs are results of an inherent genetic make-up or acquired from the exposure of pathological OA inflammatory environment. A small fraction of non-weight bearing human articular cartilage from non-OA subjects and OA patients were harvested during the arthroscopy session. Patients (n=11) were selected based on the grade 4 osteoarthritis according to the Kleegren and Lawrence score system, and five cartilage samples were obtained from nonosteoarthritic donors undergoing knee surgery or arthroscopy due to the sports injury. The optimised enzymatic digestion and serial plating methods were used to generate cartilage-derived MSCs. The differences in biological features of OA compared to non-OA C-MSCs as well as that of non-OA C-MSCs cultured in OA synovial fluid were investigated through a series of proliferation, cell cycle and apoptosis assays. The secretome profile and the global gene expression were performed through cytokine antibody arrays and microarray, respectively. Mesenchymal stem cells were successfully generated from the human OA cartilage tissues along with non-OA cartilage. As compared to the human non-OA C-MSCs, the counterpart from OA exhibited compromised cell qualities in term of ill-defined morphology specifically at late passages, lower colony forming ability, reduced chondrogenesis when induced, a higher tendency towards osteogenic and adipogenic differentiation. However, the immunophenotypic profile between these two groups remained relatively same. Additionally, human OA C-MSCs also demonstrated slower growth kinetics, prolonged doubling time, increased susceptibility to senescence especially at late passages, reduced proliferation and poor immunosuppressive ability against T cells. It was also observed that during the in vitro culture expansion, the human OA C-MSCs underwent escalated level of cellular senescence in late passage (80%), apoptosis (i.e. 18.33±0.1% early apoptosis, 6.46±0.2% late apoptosis at passage 3 and 20.09±0.1% early apoptosis, 8.42±0.2% late apoptosis at passage 6), exhibited G0/G1 cell cycle arrest (i.e. 78.68±3.17% of cells in G0/G1 phase, at passage 3 while passage 6 had 93.23±2.64% of cells in G0/G1 phase) with a secretome profile that reveals the downregulation of anti-inflammatory cytokines such as IL-1, IL-6, and IL-10, as well as aberrations in gene expression. Analysis of OA synovial fluid indicated with presence of proinflammatory cytokines that associated with OA pathophysiology while pre-treated non-OA C-MSCs with OA synovial fluid exhibited increased apoptosis (i.e. 28.42±0.66% early apoptosis and 12.11±0.47% late apoptosis) and inhibition of proliferation via cell cycle arrest (i.e.78.62±4.38% of cells in G0/G1 phase and 12.42±1.53% of cells in S phase). These findings suggest that the catabolic and inflammatory agents in the synovial fluid could be implicated in cartilage tissue degradation, and may also be involved in the alteration of the inherent genetic makeup of cartilage tissue-resident MSCs which is evident from the aberrant gene expression. The microarray-based gene expression analysis of OA C-MSCs indicated dysregulation of essential genes of cell proliferation and survival, whereas the gene expression of non-OA MSCs treated with OA synovial fluid revealed dysregulation of cartilage metabolism. The KEGG pathway analysis based on the dysregulated gene expression showed the involvement of several key signalling pathways especially Wnt signalling, cell adhesion molecule pathway, Ras signalling pathway, cytokine-cytokine receptor interaction pathway. In conclusion, the biological features of OA C-MSCs are negatively affected by OA disease. It could be possible that the inflammatory condition of OA synovial fluid impedes the functional properties of cartilage tissue-resident MSCs. Thus, treatment strategies for OA should be strategized by allotting an appropriate concern to the inflammatory condition that limits the function of tissue stem cells and therapeutically transplanted stem cells.